(untitled) (Swiss Medical Weekly, 2017)
AIMS We aimed to evaluate the interest of adult inpatients and selected outpatients in engaging in a large, real-life, hospital-based, genomic medicine research project and in receiving clinically actionable incidental findings. METHODS Within the framework of the cross-sectional Institutional Biobank of Lausanne, Switzerland, a total of 25 721 patients of the CHUV University Hospital were systematically invited to grant researchers access to their biomedical data and to donate blood for future analyses, including whole-genome sequencing. Multivariable logistic regression analysis was used to identify personal factors, including age, gender, religion, ethnicity, citizenship, education level and mode of admission, associated with willingness to participate in this genomic research project and with interest in receiving clinically actionable incidental findings. RESULTS The overall participation rate was 79% (20 343/25 721). Participation rate declined progressively with age, averaging 83%, 75%, 67% and 62% in patients aged <64 years (n = 13 108), ≥64 years (n = 12 613), ≥80 years (n = 4557) and ≥90 years (n = 1050), respectively. Factors associated with participation substantially differed between age strata. Patients less likely to participate included women (odds ratio 0.86, [95% confidence interval 0.79–0.95] and 0.78 [0.71–0.85] before and after age 64, respectively), non-Swiss (0.81 [0.74–0.90] and 0.58 [0.52–0.65]) and those admitted through the emergency ward (0.88 [0.79–0.98] and 0.66 [0.60–0.73]). Religion and marital status were associated with participation among patients aged <64 years. A total of 19 018 (93%) participants were willing to be re-contacted for incidental findings. A high education level was associated with higher participation rate, but not with higher willingness to receive incidental findings within the population who had agreed to participate. CONCLUSION A large proportion of adult patients, even among the elderly, are willing to actively participate and receive incidental findings in this systematic hospital-based precision and genomic medicine research program with broad consent.